Pemberdayaan Orang Tua sebagai Upaya Preventif Kejadian Putus Sekolah melalui Penguatan Pemahaman Urgensi Pendidikan dan Manajemen Karir Anak - Gozin Najah Rusyada; Ceriyani Miswaty, Titik; Nurul Hayati, Ridha; Kudus Pranasa, Risyaf; Ardiansyah, Lalu Yayan (Insan Kreasi Media, 2023)
The government's efforts to reduce the dropout rate through the scheme of increasing the allocation of the State Budget (APBN) for the education sector have not yet borne fruit. This is because the dropout rate in Indonesia in 2023 is still relatively high at every level and even increased compared to the previous year. This shows that the economy is not the main factor in dropping out of school. the main factor in dropping out of school in Indonesia is the low understanding of parents regarding the importance of school and the lack of parental supervision of children. This service activity aims to increase parents' knowledge regarding the importance of education and understanding the basics of children's career planning through socialization methods. The service method uses the Participatory Action Research model with three stages: preparation, implementation, and evaluation. The results of this service activity show that this activity is able to (1) increase participants' understanding of the importance of education, and (2) increase participants' understanding of children's career management.